Autologous bone marrow-derived mesenchymal stromal cells in the treatment of fistulising Crohn's disease. Issue 6 (21st January 2011) - Ciccocioppo, Rachele; Bernardo, Maria Ester; Sgarella, Adele; Maccario, Rita; Avanzini, Maria Antonietta; Ubezio, Cristina; Minelli, Antonella; Alvisi, Costanza; Vanoli, Alessandro; Calliada, Fabrizio; Dionigi, Paolo; Perotti, Cesare; et al.
Abstract : Objective: External fistulas represent a disabling manifestation of Crohn's disease with a difficult curability and a high relapse rate despite a large therapeutic armamentarium. Stem cell therapy is a novel and promising approach for treatment of chronic inflammatory conditions. We therefore investigated the feasibility, safety and efficacy of serial intrafistular injections of autologous bone marrow-derived mesenchymal stromal cells (MSCs) in the treatment of fistulising Crohn's disease. Patients and methods: We enrolled 12 consecutive outpatients (eight males, median age 32 years) refractory to or unsuitable for current available therapies. MSCs were isolated from bone marrow and expanded ex vivo to be used for both therapeutic and experimental purposes. Ten patients (two refused) received intrafistular MSC injections (median 4) scheduled every 4 weeks, and were monitored by surgical, MRI and endoscopic evaluation for 12 months afterwards. The feasibility of obtaining at least 50×10 6 MSCs from each patient, the appearance of adverse events, and the efficacy in terms of fistula healing and reduction of both Crohn's disease and perianal disease activity indexes were evaluated. In addition, the percentage of both mucosal and circulating regulatory T cells expressing FoxP3, and the ability of MSCs to influence mucosal T cell apoptosis were investigated. Results: MSC expansion was successful in all cases; sustained complete closure (seven cases) or incomplete closure (three cases) of fistula tracks with a parallel reduction of Crohn's disease and perianal disease activity indexes (p<0.01 for both), and rectal mucosal healing were induced by treatment without any adverse effects. The percentage of mucosal and circulating regulatory T cells significantly increased during the treatment and remained stable until the end of follow up (p<0.0001 and p<0.01, respectively). Furthermore, MSCs have been proven to affect mucosal T cell apoptotic rate. Conclusions: Locally injected MSCs represent a feasible, safe and beneficial therapy in refractory fistulising Crohn's disease.